The agricultural system in the holy Quran and its effects on development: Al-Ittifaq foundation in Indonesia as a case study / Abdelrahman Monis - Abdelrahman , Monis (2018)
This study aims at investigating the agricultural system as mentioned in the Qur’an along with its impact on development. It also aims at investigating the stand of Al-Itifaq Institution to ensure that the institution grasps well agriculture and its system. Besides, this study explores the extent to which this institution adopts the agricultural system’s criteria as mentioned in the Qur’an; thus, recognizing its criteria for achieving development. These aims are based on the occurence of some negative impacts on many in society. This can be attributed to the ignorance many people have about Qur’anic concepts, especially those related to agriculture and its system. To achieve the objectives of the study, the researcher adopted an analytical inductive method through collecting the Qur’anic verses related to agriculture and its system; discussing and analysing them in the light of the books of tafsir (explanation of the Qur’an), and relating these to existing scientific research. In addition, the researcher used the applied descriptive reseach method, which is based on preparing questionnaires and conducting personal interviews with officials from the Itifaq Institution to collect practical information on the topic of this study, and then to analyze these gathered pieces of information. The present study proved that agriculture and its system were not limited to laboratory research only, and that they had a root in the Qur’an. This root comes in several forms: setting examples, scientific inimitability, and divine commands in the form of either an ordainment or a prohibition. The study also confirmed that agriculture is vital to all creatures including man and that human life at any spot on earth starts where the soil is fertile as well as the existence of water and vegetation. The study also confirmed that the elements of the agricultural system can be divided into main elements such as winds, clouds, water and land, and seconday elements such as man, animals, and other living creatures. All these elements are indispensible, especially those which fall under the main category, the winds in particular. The study reconfirmed that the most significant impact of the agricultural system is that which touches on the faith aspect, then the psychological aspect, followed by the agricultural aspect with its two sub-aspects: the environmental and the economic. It also confirmed that the positive and or the negative impact can be dependent on or independent of man’s choice. The field study confirmed that society needs more agriculture-related studies. No doubt, the expreience of the earlier researchers as well as modern technology cannot be overlooked. The study also confirmed that all creatures need one another; therefore, Allah the Almighty has given man mental power along with some physical strength which is sufficient for making him capable of running and managing some parts of the agricultural operation. Similarly, Allah the Almighty has given animals huge physical power along with very limited mental power to help man excute some operations. Finally, Allah has put some of His secrets in the other living creatures that help carry out the agricultural operation from the beginning to the end; it is Allah Who controls all! The study reaffirmed that achieving development is the society’s cause. Thus, to achieve development, all elements of the society, including agriculture specialists, must take part and contribute thereto.